HOUSEHOLD’S RESPONSES TO THE ROLES OF TREES AS WIND BREAKER IN DUTSE LOCAL GOVERNMENT AREA OF JIGAWA STATE, NIGERIA - Ilu, K. J.; Salami, K. D.; Gidado, A. H.; Muhammad, Y. K.; Bello, Ahmed (FUDMA JOURNAL OF SCIENCES, 2020)
Wind is a natural process through which air moves in mass from high pressure areas to low pressure areas. There is no doubt when not obstructed can damage several natural features and human-made structures beyond repairs. However, in an open landscape trees provide the most effective protection compared to other biological wind control measures. This study investigated household’s responses to the roles of trees as wind breaker in Dutse Local Government Area of Jigawa State, Nigeria. The data were collected with the aid of structured questionnaires coupled with oral interview schedules. A total of five (5) wards namely: Chamo, Dundubus, Limawa, Kaci and Dutse were randomly selected based on the havoc caused by wind in the areas. Fifteen villages were randomly selected from five wards. Thirty (30) respondents were randomly selected from each of the chosen wards; thus, one hundred and fifty (150) respondents make up the sample size for this research while the data were subjected to descriptive statistics analysis. Multistage random sampling was used for this research. The results from this study showed that dominant tree (67%), deforestation (62%), fuel-wood (60%) and tree planting (60%) had the highest percentage. In conclusion, Dutse people are greatly depend on the use of fuel-wood for their domestic uses and also aware of mitigating methods. Therefore, enlighten of the people on the effect of deforestation and also alternative sources of biofuel must be provided in order to maintain ecological balance, and reduce high level of deforestation in the study areas.